Performance of cowpea cultivars when grown as an intercrop with maize of contrasting maturities - Ewansiha, S.U.; Kamara, A.; Onyibe, J.E. (Informa UK Limited, 2014)
A field trial was conducted during the rainy seasons of 2008 and 2009 at Samaru in northern Guinea savannah of Nigeria to determine the performance of semi-determinate and indeterminate cowpea cultivars intercropped with extra early, early and late maize cultivars. The trial was laid out in a randomized complete block design (RCBD) having treatments arranged as a split-plot factorial. Transmitted radiation was reduced by 49–63% due to shading by the maize plants. Similarly, intercropping cowpea with maize reduced intercepted radiation, fodder yield and grain yield of cowpea by 59–70%, 39–51% and 45–62%, respectively. Intercepted radiation and yields of intercropped cowpea were lower for late maize which maintained high leaf area over a longer period of time. This is supported by the higher plant height, higher leaf area index (LAI) and reduced transmitted radiation recorded in late maize compared with extra early and early maize. Extra early and early maize were less competitive with cowpea because of shorter period of association in addition to permitting higher radiation. Crop value of maize plus cowpea was higher than that of sole cowpea ($2616.8 vs. $1218.7 ha?1) because higher combined yield was achieved by a more efficient use of resources in the intercrop. Therefore, cowpea cultivar may be intercropped with extra early maize.